Factors that foster Latina, English language learner, non-traditional student resilience in higher education and their persistence in teacher education - Morales, Amanda Irwin Rodriguez (Kansas State University, 2011)
This qualitative case study focused on 11 non-traditional, ELL, Latinas within a community-based, teacher education program. The purpose of the study was: (a) to explore the various internal characteristics and external factors that foster Latina, English language learner (ELL), non-traditional students’ resiliency in reaching and remaining in college and (b) to determine what ways these internal characteristics and external factors influenced participants’ desire to pursue and ability to persist in teacher education. The researcher utilized two primary sources of data, (1) an autobiographical, qualitative survey, and (2) individual in-depth, semi-structured interviews. As a secondary source, the researcher used academic documents to provide context for student success in the program. The internal characteristic of sense of purpose and a future (demonstrated in participants’ determination, identity, and responsibility) proved to be most protective for participants’ resiliency. Caring relationships (with the features of: consejos (advice or homilies), quality not quantity, and high expectations in the context of care) proved to be the most significant external factor for fostering participant resiliency. The study also identified the overarching emergent theme of advocacy inspired by hardship found among participant discourse. Within this theme, findings indicated that, as a result of their cultural and experiential understandings, participants were able to enact culturally responsive teaching with their Latino/a students. Furthermore, participants demonstrated a strong sense of agency to improve the education outcomes of culturally and linguistically diverse (CLD) students and a desire to advocate specifically on behalf of ELL Latino/as students.
Keywords: Resiliency; Latina; Teacher education; English Language Learner (ELL); Non-traditional; Persistence; Higher Education (0745); Multicultural education (0455); Teacher Education (0530)